Household Food And Water Processing Models To Reduce Stunting Prevalence In Toddlers In Indonesia - Fadilah, Mariatul; Andrean, Andy; Trinita, Melros (Advances in Social Sciences Research Journal, 2020)
Stunting (suboptimal linear growth, defined as a Z-score below 2 standard deviations (SD) of the median WHO child growth standard for height/age) is the most common form of child malnutrition, affecting an estimated 150.8 million children under age 5 (22.2 percent) worldwide in 2017. The purpose of this study was to find a model of reducing the prevalence of stunting of children under five in Palembang in terms of the Health Belief Model through food processing and household drinks. This type of research is observational analytic research and cross-sectional study design. The population in this study were all mothers of children under five (0-59 months) who examined their children in the working area of the Palembang city health center. each increase in 1 unit of vulnerability perception increases 0.226 units of household food and water processing behavior (p-value = 0.001). The perception of seriousness shows no significant correlation with the estimated value of 0.033 (p-value = 0.269). On the perception of benefits, each increase of 1 unit will increase 0.123 units of household food and water processing behavior (p-value 0.001). Obtained the perception of obstacles not significantly correlated with household food and water processing behavior with a p-value of 0.342. The acting signal component also shows the results that there is no significant correlation with household food and water processing behavior with a p-value of 0.113. Every increase of 1 unit of ability/efficacy increases 0.570 units of household food and water processing behavior (p-value = 0.001). In this study, it was also found that there was no significant correlation of household food and water processing behavior with stunting in Palembang with a p-value of 0.511. In conclusion, the perception of vulnerability and ability/efficacy shows a positive correlation with household food and water processing behavior, and the component of cues to act that most influences household food and water processing behavior is self-awareness.